Electrical Insulation Characteristics Of P Epdm Blends With Aln, Al2o3 And Rganoclay Nanofillers - Mansor, Noor Syazwani (2015)
Insulator failure as a result of ageing or contamination flashover is the major cause of line outages. When the surface of an insulator is contaminated under wet condition, the surface layer become conductive and caused leakage current to flow on the layer. The insulator exposed to the leakage current will eventually experience a severe damage. Recently, the outdoor insulation made from glass or porcelain which is used in power system since long time ago have gradually replaced with polymeric insulators. Thus, many research has been conducted in polymeric insulators mainly PP/EPDM. Although the research on the PP/EPDM has been carried out, so far there are no reported studies on dielectric properties and resistance and erosion to tracking with various filler loading of PP/EPDM blends. Thus, in this project, the investigation on dielectric properties and resistance and erosion to tracking of the PP/EPDM blends with three types of nanofillers such as Al2O3, AlN and organoclay was carried out. The percentage of filler loading for each specimen is 2 vol%, 4 vol%, 6 vol% and 8 vol%. The effects of Al2O3, AlN and organoclay nanofillers with various loading on dielectric properties, resistance and erosion to tracking, thermal conductivity and hydrophobicity of PP/EPDM blends were experimentally investigated. The result revealed that the addition of 2 vol% of Al2O3 and organoclay nanofillers into the PP/EPDM blend has increased the dielectric strength by 4.13% and 4.33%, respectively from that without nanofiller. In the other hand, the AlN has decreased the dielectric strength of PP/EPDM blends by 1.79%. The 2 vol% of Al2O3 nanocomposites has slightly same dielectric constant and higher dielectric strength with the unfilled PP/EPDM. The results revealed that addition of nanofillers significantly improved the resistance and erosion to tracking. The mass loss and erosion depth of the PP/EPDM nanocomposites decreased with the increase in filler loading. The PP/EPDM filled with 4 vol% organoclay and 6 vol% Al2O3 odward is considered to have hydrophilic surfaces. The PP/EPDM with AlN nanofiller reduces the hydrophobicity condition of the material when the concentrations of the filler increased and maintained the hydrophobic surface condition at 8 vol%.